2022
DOI: 10.1039/d2ob01080a
|View full text |Cite
|
Sign up to set email alerts
|

Electrosynthetic C–F bond cleavage

Abstract: Fluorinated organic compounds display attractive physical, chemical, and biological properties and are common among pharmaceuticals, agrochemicals and materials. The significant bond strength of the C-F bond results in chemical inertness...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 115 publications
1
14
0
Order By: Relevance
“…From Figure 4 and Figure 5, we can obvious observed that the T 5% and T 10% of the PBPD‐2 and PBFD‐2 increased with the increase of temperature, which should be due to the increase of N‐heterocyclic structures density and thermal properties with the deepening of reaction degree. Furthermore, PBFD‐1, PBFD‐2 exhibited more excellent thermal performance than PBPD‐1, PBPD‐2 and PBAD‐1, which attributed to the stronger bond energy of C−F bond, [28] and the −CF 3 groups had strong electron absorption preventing the further movement of the chains. Compared with the previous studies in Table 4, resin PBPD and PBFD had similar thermal stability [30]…”
Section: Resultsmentioning
confidence: 96%
“…From Figure 4 and Figure 5, we can obvious observed that the T 5% and T 10% of the PBPD‐2 and PBFD‐2 increased with the increase of temperature, which should be due to the increase of N‐heterocyclic structures density and thermal properties with the deepening of reaction degree. Furthermore, PBFD‐1, PBFD‐2 exhibited more excellent thermal performance than PBPD‐1, PBPD‐2 and PBAD‐1, which attributed to the stronger bond energy of C−F bond, [28] and the −CF 3 groups had strong electron absorption preventing the further movement of the chains. Compared with the previous studies in Table 4, resin PBPD and PBFD had similar thermal stability [30]…”
Section: Resultsmentioning
confidence: 96%
“…Dehalogenation of the benzylic CF 3 group in (1,1,1)-trifluoromethylbenzene was accomplished in around 80% conversion to give a mixture of defluorinated toluene products, representing one of the few examples of C–F bond cleavage under electrochemical conditions. 35 As demonstrated in a control experiment, the Sm catalyst enabled a switch in product selectivity for the reduction of (2-halophenyl)allyl ethers. While reduction of (2-bromophenyl)allyl ether and (2-chlorophenyl)allyl ether in the absence of the Sm(III) complex resulted in the dehalogenated open-chain product with only a trace amount of the cyclized product, the addition of SmCl 3 resulted in 3-methyl-2,3-dihydrobenzofuran in 80% yield.…”
Section: Compounds Containing Carbon–halide Bondsmentioning
confidence: 93%
“…The existing methods for the selective C–F activation of CF 3 groups can be classified into four categories: (1) Lewis-acid-promoted formation of a difluorocarbocation intermediate; (2) metal or electrochemical-induced formation of a difluorocarbonanion intermediate; (3) single electron transfer (SET) or spin-center shift pathways leading to a difluorocarboradical intermediate; and (4) a carbene strategy catalyzed by rhodium or silver (Scheme a). Using these strategies, besides defluoroalkylation and hydrodefluorination of trifluoromethylarenes, Zhang’s group reported selective defluoroarylation and Zhang’s group later developed a method for the selective defluorination bifunctionalization of trifluoromethyl aromatics with active alkenes . Although these strategies are now well-established, the selective C–F activation and defluorination functionalization of the CF 3 motif continue to pose challenges due to the high energy of C­(sp 3 )–F bonds and the need to prevent excessive defluorination.…”
Section: Introductionmentioning
confidence: 99%